1631 Va. Acts 173, Act 51 - (:unkn) unknown (My University, 1631)
All men that are fitting to bear arms, shall bring their pieces to the church upon pain of every offence, of the mayster allow not thereof to pay 2 lb. of tobacco, to be disposed by the church-wardens, who shall levy it by distress, and the servants be punished.
Keywords: REQUIRED POSSESSION